How and Why the Per Se Rule Against Price-Fixing Went Wrong - Sheldon Kimmel (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2006)
Most scholars believe the Supreme Court dropped its per se rule against price-fixing in Appalachian Coals (1933), re-instituting that rule in Socony-Vacuum (1940), but that the rule ignored "reasonableness" until BMI (1979), and that Maricopa (1982) relied on Socony to step back from "reasonableness" again. However, the view that Socony's per se rule had nothing to do with "reasonableness" came from unreasonably ignoring Socony's comments on Appalachian Coals, which came from misunderstanding Appalachian Coals by ignoring the economic implications of the facts the district court found. Those implications show that Appalachian Coals, Socony, and BMI all gave the same price-fixing rule.
Keywords: 330